Characteristics Upon Presentation of Patients with Type 2 Macular Telangiectasia in Puerto Rico - González-Martínez, Orlando G.; Ortiz, Jan; Quiñones, Sebastián; Alicea, Jonathan G.; Guevara, Francisco; Pérez, Alejandro; Pappaterra, Mariella; Requejo-Figueroa, Guillermo A.; Amaral, Claudia; Rivera-Grana, Erick; et al. (Puerto Rico Health Sciences Journal, 2022)
Objective: To describe the systemic disease associations and clinical features upon initial presentation of a cohort of patients with type 2 macular telangiectasia who live in Puerto Rico. Methods: A retrospective review of patients with macular telangiectasia was performed in 4 private retina practices in Puerto Rico. The demographic and clinical characteristics were recorded. Results: Twenty-one patients who were diagnosed with macular telangiectasia were included in the analysis. The median age of presentation was 62 years; 86% were female, and all patients were Hispanics. The median visual acuity at presentation was 20/50. A prior medical diagnosis of type II diabetes mellitus was found in 15 (71.4%) patients, essential hypertension in 12 (57.1%), and dyslipidemia in 9 (42.9%). All patients had bilateral disease. The most common ocular findings were the presence of right-angle vessels in 32 (76.2%) eyes and angiographic hyperfluorescence temporal to the fovea, found in 22 (52.4%) of the affected eyes. One eye had evidence of choroidal neovascularization. Conclusion: Our cohort showed a higher prevalence of type 2 diabetes in patients with type 2 macular telangiectasia than in other cohorts. It also supports the findings of other studies showing that macular telangiectasia patients are more likely to have type 2 diabetes and hyperlipidemia. However, the increased prevalence of diabetes and hyperlipidemia may be due to selection bias, and further studies are needed to assess the significance of these findings.